2019
DOI: 10.1111/cas.13898
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node resection induces the activation of tumor cells in the lungs

Abstract: Lymph node (LN) dissection is a crucial procedure for cancer staging, diagnosis and treatment, and for predicting patient survival. Activation of lung metastatic lesions after LN dissection has been described for head and neck cancer and breast cancer. Preclinical studies have reported that dissection of a tumor‐bearing LN is involved in the activation and rapid growth of latent tumor metastases in distant organs, but it is also important to understand how normal (non‐tumor‐bearing) LN resection influences sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…32,59,60 In addition, our research group has shown that LN dissection induces activation of tumor cells that have metastasized to distant organs. 32,39,41,42 In summary, the rationale for LDDS targeting metastatic LN is to treat tumor tissue within metastatic LN, prevent distant metastasis of tumor cells from metastatic LN, avoid vascular damage, nerve damage, incisional infection, lymphedema 32,61 associated with LN removal, and the activation of tumor cells in distant organs associated with LN dissection and minimizing side effects. Therefore, the injection duration of chemotherapy drugs using the LDDS will be less than for the intratumoral or intralesion methods used in the clinic, and systemic toxicity will be less than for tumor-targeted therapy or In the future, optimizing factors, such as particle size, molecular weight, surface charge, lipophilicity, concentration, and the surface modification of biomaterials 32,46 to provide optimal osmolality and viscosity, will enable immunological strategies that can efficiently deliver biomaterials to these immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,59,60 In addition, our research group has shown that LN dissection induces activation of tumor cells that have metastasized to distant organs. 32,39,41,42 In summary, the rationale for LDDS targeting metastatic LN is to treat tumor tissue within metastatic LN, prevent distant metastasis of tumor cells from metastatic LN, avoid vascular damage, nerve damage, incisional infection, lymphedema 32,61 associated with LN removal, and the activation of tumor cells in distant organs associated with LN dissection and minimizing side effects. Therefore, the injection duration of chemotherapy drugs using the LDDS will be less than for the intratumoral or intralesion methods used in the clinic, and systemic toxicity will be less than for tumor-targeted therapy or In the future, optimizing factors, such as particle size, molecular weight, surface charge, lipophilicity, concentration, and the surface modification of biomaterials 32,46 to provide optimal osmolality and viscosity, will enable immunological strategies that can efficiently deliver biomaterials to these immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, all in vivo experiments were carried out on mice under general anesthesia (2.5% isoflurane in oxygen), and great care was taken to reduce animal suffering. 32 , 39 , 40 , 41 , 42 The day on which the SiLN was inoculated with tumor cells was defined as day 0 I (Data S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After depilation and skin disinfection, a minimally invasive approach was used for incision of the skin and exposure and extirpation of the tumor-bearing SiLN on day 3 post-inoculation for both cell types. Metastasis to the PALN and lung were assessed using the IVIS 18 at 6 h and on days 3, 6 and 9 post-inoculation of KM-Luc/GFP cells and days 7, 14, 21 and 28 post-inoculation of FM3A-Luc cells. Luciferin (15 mg/kg; Promega, Madison, WI, USA) was injected intraperitoneally into each mouse.…”
Section: Methodsmentioning
confidence: 99%
“…The excised organs from mice in the control group ( n = 4) were obtained on day 6 post-inoculation. Embedded specimens were serially sectioned (2 µm) and stained with EM or HE or immunostained for CD31 or Ki67 18 . Anti-CD31 staining to identify vascular endothelial cells was performed using an automated processor (Discovery, Ventana Medical Systems, Inc., Tucson, AZ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer remains one of the leading causes of mortality worldwide, and most cases are due to lymph node (LN) metastasis [1]. To date, many measures have been developed to combat this trend, with remarkable therapeutic outcomes [2][3][4][5]; however, there is still a growing number of physical and emotional side effects associated with these protocols [6,7]. The destruction of tumour metastasis under hyperthermia has been investigated in the past few years as a non-invasive treatment method [8,9].…”
Section: Introductionmentioning
confidence: 99%